-52+5k=6(-8k+9)

Simple and best practice solution for -52+5k=6(-8k+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -52+5k=6(-8k+9) equation:


Simplifying
-52 + 5k = 6(-8k + 9)

Reorder the terms:
-52 + 5k = 6(9 + -8k)
-52 + 5k = (9 * 6 + -8k * 6)
-52 + 5k = (54 + -48k)

Solving
-52 + 5k = 54 + -48k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '48k' to each side of the equation.
-52 + 5k + 48k = 54 + -48k + 48k

Combine like terms: 5k + 48k = 53k
-52 + 53k = 54 + -48k + 48k

Combine like terms: -48k + 48k = 0
-52 + 53k = 54 + 0
-52 + 53k = 54

Add '52' to each side of the equation.
-52 + 52 + 53k = 54 + 52

Combine like terms: -52 + 52 = 0
0 + 53k = 54 + 52
53k = 54 + 52

Combine like terms: 54 + 52 = 106
53k = 106

Divide each side by '53'.
k = 2

Simplifying
k = 2

See similar equations:

| (16x-14y)+4(5y-3x)= | | 2x(30-10)=0 | | (x^2-7)(x+2)=0 | | .5x^6-.5x^5=0 | | X*(5/3)*X=166 | | 50-6(X)=2 | | .5x-8=1 | | 50-6(6)= | | 49-4x=13-8x | | .5x-8=17 | | 64+10x=-12(1-4x) | | .5x^5-.5x^5=0 | | 1/3x=7/8 | | -11-11v=-2(v+1) | | 850=525+.21x | | 20+4y=9y | | 5y-3x=-4 | | 49c^2-9p^2= | | 6x^2-24=7x | | -4(-5x-1)=-59+11x | | 5*20-x+76=172 | | v+8=5v-12 | | -8r-22=-5(3r-11) | | 9(q+2)-3(q+3)=9 | | x-105=6x | | .33x+7=1 | | -18-8x=-10(x+4) | | f(x)=15x^4+8x^3-18x^2+1 | | m-1=-13+3m | | 3/103/4 | | 3(2x-5)+24-4x=9 | | 25x^2=-45x-18 |

Equations solver categories